2020
DOI: 10.1111/ecc.13322
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters in childhood cancer survivors in Korea: A latent class analysis

Abstract: , but higher than those in developing Asian countries (Bao et al., 2010). The number of childhood cancer survivors (CCS) is steadily increasing, but research concerning late effects or symptoms, their antecedents and their consequences is rare in Korea. More than 80% of children treated for cancer survive at least five years due to advanced and aggressive treatment protocols. However, late effects have been reported among cancer survivors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…However, there is limited research on childhood cancer and the experience of late effects during survivorship, especially in Korea. In our prior quantitative research, it was found that more than 50% of CCS in Korea experience late effects of cancer treatment and that there is a need for tailored interventions for CCS with different numbers and intensities of late effects [25]. Yet, this prior research was fractional and used generic quantitative measures, which limited the ability of CCS to report real experiences that are significant to them [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited research on childhood cancer and the experience of late effects during survivorship, especially in Korea. In our prior quantitative research, it was found that more than 50% of CCS in Korea experience late effects of cancer treatment and that there is a need for tailored interventions for CCS with different numbers and intensities of late effects [25]. Yet, this prior research was fractional and used generic quantitative measures, which limited the ability of CCS to report real experiences that are significant to them [26].…”
Section: Introductionmentioning
confidence: 99%
“…Sleeping disturbances, fatigue, pain, worries, fears and nervousness were prevalent in over 30% of patients, DT scores and information on whether or not psychooncological help was requested was available for all patients. Previous studies also selected the most prevalent symptoms to perform analysis [21,[37][38][39]. We identified the appropriate number of classes using the Akaike information criterion (AIC),…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In the present exploratory analysis, we aimed to investigate the association of the overall distress score, as measured with the distress thermometer (DT; [20]), with the individual decision for or against psycho-oncological support, sleeping disturbances, fatigue, pain, worry, fears, and nervousness. The objective is to J o u r n a l P r e -p r o o f distinguish subgroups based on different distress profiles to help health care providers identify patients in need and tailor subsequent treatments [21]. Based on our clinical observation, we hypothesized that patients with primarily physical challenges (pain, sleeping disturbances, fatigue), but no emotional problems, will be more likely to decline psycho-oncological help, while all subgroups with high emotional distress will request psycho-oncological services.…”
Section: Introductionmentioning
confidence: 99%
“…CCS are at risk for adverse late effects, including peripheral neuropathy, respiratory, cardiovascular, metabolic, skeletal, reproductive, and neurocognitive disorders, due to the aggressive and toxic treatments received in childhood (Huang et al, 2013; Krull et al, 2018). In our previous study, we used the 32‐item Memorial Symptom Assessment Scale (MSAS) to identify symptoms among CCS, who reported 13 symptoms on average, including difficulty concentrating, lack of energy, worrying, drowsiness, and pain (Hong et al, 2020). These disorders and associated symptoms occur more often in CCS than in their siblings or peers (Norsker et al, 2018; Schulte et al, 2021; Suh et al, 2020) and are shown to increase with age (Hudson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Korean, most CCS have regular follow‐ups (every 6 months to 1 year) with the hematologist who provided their cancer treatment until they are declared to be survivors (5 years posttreatment). These follow‐ups are usually brief and focus on the signs and symptoms of cancer relapse, not on managing late and long‐term effects of cancer treatment, psychological symptoms or health behaviors that may contribute to poor HRQOL (Hong et al, 2020). Examining contributory factors is important for healthcare professionals in planning, developing, and delivering appropriate interventions specific to CCS to improve HRQOL (Wakefield et al, 2010).…”
Section: Introductionmentioning
confidence: 99%